An index for the estimation of chicken adaptability to free-range farming systems of different slow-growing genotypes - Mattioli, Simona; Menchetti, Laura; Angelucci, Elisa; Cartoni Mancinelli, Alice; Dal Bosco, Alessandro; Madeo, Laura; Di Federico, Francesca; Bosa, Luigia; Moscati, Livia; Castellini, Cesare (Frontiers in Animal Science, 2025)
IntroductionEstimation of chicken adaptability to an extensive rearing system (ERS) is a complex issue. Many aspects should be considered: natural and/or welfare-based behaviors, kinetic and foraging attitude, resistance to environmental changes (i.e., thermotolerance), and resistance to disease. However, it is necessary to find a rapid and straightforward way to define the degree of adaptation of a chicken genotype in a commercial farm context. With this purpose, the objective of the present research was to develop an index of adaptability constituted by few and simple traits.Material and methodTwo hundred chickens of four different slow-growing genotypes (SGs; 25 chickens x 2 replicates x genotype) were reared outdoors: Red JA57 (RJ), Naked Neck (NN), Lohmann Dual meat-type (LD), and an Italian crossbreed (Robusta Maculata x Sassò, CB). Behavioral observations were recorded 2 times/week on outdoor pens from 36 to 81 days, whereas plumage condition, hock burns, footpad dermatitis, blood parameters, proximate composition, and technological traits of breast and drumstick meat were recorded at slaughter age (81 days) from 15/chickens per genotype. On-farm productive performance was recorded weekly. The nearly 200 variables collected were classified into four pillars (i.e., behaviors, body conditions, meat quality, in vivo health) and reduced to nine main variables by using discriminant analysis (DA) and principal component analysis (PCA). The index score was calculated as the sum of the variables weighted by the loading obtained in the final PCA. Finally, the Cronbach’s alpha test was used to measure the internal consistency and reliability of the index.ResultsThe present investigation demonstrated that measuring only nine traits (breast malondialdehyde, breast yield and live weight, allo-grooming, resting and running behaviors, n-6 polyunsaturated fatty acids [PUFA], saturated fatty acids [SFA] of drumstick, blood PUFA, Heterophile/Lymphocyte ratio) of different pillars could be an efficient, rapid, and economical strategy to assess the adaptability of chicken genotypes to ERS.ConclusionThe final classification showed that CB and LD genotypes had the worst indices, whereas NN and RJ showed the best ones. However, it is necessary to verify the reliability of the present approach in different rearing conditions and with other genetic strains.